ASAS PRADUGA RECHTMATIGE DALAM PERATURAN PERIZINAN USAHA PERDAGANGAN - Ronny Winarno (Arena Hukum, 2018)
Abstract Regulation of the Minister of Trade of the Republic of Indoneisa No.36/M-Dag/Per/9/2007 concerning the Issuance of Trading Business License (SIUP), regulates every company, cooperative, partnership or individual company which conducts trade business must have SIUP issued by permit agency. SIUP serves as a proof of trade business and aims to provide business legality. According to Law No.5 of 1986 on the State Administrative Court (TUN Judiciary), SIUP is categorized by TUN's concrete, individual and final decisions. SIUP is binding and has legal force. Here is the proof method, if the SIUP is sued for its legal validity, then the principle of presumption of rechtmatige applies. The aim is to prove that SIUP as a TUN decision can tested and decided by the TUN court in accordance with article 48 of Law No.5 of 1986, where court will resolve the TUN dispute if all administrative efforts concerned have been used. As long as there is no decision of TUN court in the form of inkracht, which declares null and void on the decision of TUN, and then SIUP shall remain valid (rechtmatige). So the position of the presumption principle of rechtmatige can be a determinant of whether there is an element action against the law. Abstrak Peraturan Menteri Perdagangan RI No : 36/M-Dag/Per/9/2007 Tentang Penerbitan Surat Izin Usaha Perdagangan (SIUP), mengatur setiap perusahaan, koperasi, persekutuan maupun perusahaan perseorangan yang melakukan usaha perdagang-an wajib memiliki SIUP yang diterbitkan oleh Badan Perizinan. SIUP berfungsi sebagai alat bukti usaha perdagangan dan bertujuan memberikan legalitas usaha. Menurut UU No. 5 Tahun 1986 tentang Peradilan TUN, SIUP dikategorikan sebagai Keputusan TUN yang bersifat konkrit, individual dan final. Sehingga SIUP bersifat mengikat dan memiliki kekuatan hukum. Disinilah dengan metode pembuktian, jika SIUP digugat keabsahan hukumnya, maka berlaku adanya asas praduga rechtmatige,. Tujuannya, untuk membuktikan SIUP sebagai keputusan TUN bisa diuji dan diputuskan oleh Pengadilan TUN sesuai Pasal 48 UU No. 5 Tahun 1986, bahwa pengadilan akan menyelesaikan sengketa TUN jika seluruh upaya administratif telah digunakan. Selama belum ada putusan pengadilan TUN yang bersifat inkracht, yang menyatakan batal atau tidak sah atas keputusan TUN, maka SIUP dinyatakan tetap berlaku (rechtmatige). Jadi kedudukan asas praduga rechtmatige ini bisa menjadi penentu apakah ada unsur perbuatan melawan hukum.